Burma's Transition to "Disciplined Democracy": Abdication or Institutionalization of Military Rule? - Marco Bünte (German Institute of Global and Area Studies (GIGA), 2011)
Direct military rule has become rare in world politics. Today, most military regimes have either given way to some form of democracy or been transformed into another form of authoritarianism. This article formulates an analytical framework for the detachment of militaries from politics and identifies positive and negative factors for a withdrawal. It then applies this framework to the case of Burma/Myanmar, which is an example of deeply entrenched military rule. It is argued that the retreat from direct rule has brought with it a further institutionalization of military rule in politics, since the military was able to safeguard its interests and design the new electoral authoritarian regime according to its own purposes. The article identifies the internal dynamics within the military regime as a prime motive for a reform of the military regime. Although the external environment has completely changed over the last two decades, this had only a minor impact on military politics. The opposition could not profit from the regime's factionalization and external sanctions and pressure have been undermined by Asian engagement.
Keywords: 300; military regime; civilian control; external influences; internal influences; competitive authoritarianism; Burma/Myanmar; Diktatur; Autoritäres System; Politische Entscheidung; Demokratie; Myanmar